13 Neutrophil activation at the culprit lesion in acute ST-segment elevation myocardial infarction with multiple complex coronary plaques. (9th June 2011) - Marshall, C J; Mckenzie, J L; Moccata, T; Nallaratnam, M; Blake, J; Frampton, C; Richards, M; Kettle, A J; Mcclean, D R
Abstract : Introduction: The activation of neutrophils at the culprit coronary lesion following acute plaque disruption has not been reported. We hypothesised that neutrophil activation occurs in ST elevation myocardial infarction (STEMI) prior to percutaneous intervention (PCI), and that differences in activation may be detectable locally at the culprit lesion, particularly in patients with multiple complex coronary plaques. Methods: Forty STEMI patients having primary PCI were compared to 10 controls with chronic stable angina (CSA) undergoing elective PCI. The clinical, demographic and angiographic characteristics of patients and controls are shown in Abstract 13 table 1 . The culprit lesion was sampled after passage of a guide wire across the lesion and use of a low profile sampling catheter (Multifunctional probing catheter, Boston Scientific Corporation, Natick, Massachusetts, USA) at the site of occlusion, prior to further mechanical intervention. Neutrophil activation was measured by flow cytometry using neutrophil intracellular myeloperoxidase content (MPO Index) and the expression of the β2- integrin CD11b, a leukocyte adhesion and activation marker at the culprit coronary lesion (CA), the aorta at the coronary ostium (Ao), the coronary sinus (CS), and femoral artery (FA) prior to primary PCI. A lower MPO content indicates the depletion of intracellular MPO and cell activation. Results: A marked decrease in MPO content occurred at the CA, Ao and FA in STEMI compared to elective controls (p<0.01). Furthermore, MPO content was lower at the CA (−23.1, (−25.6 to −17.1), n=37) compared to Ao (−22.0, (−24.7 to −16.2), n=37), CS (−20.6, (−24.8 to −16.9), n=30) and FA (−20.4, (−24.4 to −13.1), n=40), all p<0.001 (Abstract 13 figure 1 ). Neutrophil MPO content was correlated with CD11b expression only at the culprit CA in STEMI (r=−0.4, p=0.03, n=31) (Abstract 13 figure 2 ). Neutrophil MPO content at the CA in patients with multiple complex plaques was similar to those with a single culprit however only in those with multiple complex plaques was a correlation between MPO content and CD11b (r=−0.7, p=0.02) shown. Conclusion: In acute STEMI, neutrophils are activated systemically, regionally and locally at the culprit coronary lesion. In patients with multiple complex plaques, there may be an extended local role for the activated neutrophil following acute plaque destabilisation.